THE ACCURACY IN WRITING TITLE OF KTI AMONG FIRST GRADE STUDENTS IN D-III NURSING PROGRAM AT THE HEALTH POLYTECHNIC OF THE MINISTRY OF HEALTH, PADANG WEST SUMATERA - Zona Rida Rahayu; Redo Andi Marta (Jurnal Ilmu Pendidikan Ahlussunnah, 2022)
In order to obtain a bachelor's degree, a student had to compose KTI. Before writing the complete KTI, the students needed to focus on the title of KTI. This study investigated the method used in writing KTI titles by DIII Nursing students at the Health Polytechnic of the Ministry of Health, Padang. This study used a descriptive quantitative approach. This study results showed that the writing of KTI titles for students in the DIII Nursing study program was success. Based on the performance of text in writing the KTI title, students obtained very good and good qualifications. For very good qualification, the score was 80-95, and Good qualification range of 60 -75. There was several indicators used in this assessment, namely the originality and relevant titles, provocative, short, clear and specific, titles in the phrases form, using capital letters and without punctuation, and logical.